2019
DOI: 10.4028/www.scientific.net/msf.966.14
|View full text |Cite
|
Sign up to set email alerts
|

Precipitated Silica from Sodium Silicate by CO<sub>2</sub> on Fixed Bed Column

Abstract: The precipitated silica prepared by reaction of sodium silicate and gas CO2 on fixed bed column have been production successfully. In this study, silica from bagasse was extraction by sodium hydroxide 2N solution to produce sodium silicate solution. The sodium silicate solution was dilute by demineralize water to produce some concentration in the range of 0.33-0.98 %SiO2. Fixed bed column has a diameter of 7.5 cm with a height of 50 cm and a pH control apparatus. CO2 gas and sodium silicate liquid are both flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…9 In previous studies, it was also found that the pH of sodium silicate aqueous solution decreased as the absorbed CO 2 increased. 21,22 It can be stated that the CO 2 absorption experiment with codes A, B, and C for 5 min performed with 2% v sodium silicate aqueous solution was less than optimal. Even though the small bubbles are evenly distributed, the CO 2 barely reacts with the sodium silicate solution; as a result, there is still a lot of gas that escapes from the surface of the liquid.…”
Section: Resultsmentioning
confidence: 99%
“…9 In previous studies, it was also found that the pH of sodium silicate aqueous solution decreased as the absorbed CO 2 increased. 21,22 It can be stated that the CO 2 absorption experiment with codes A, B, and C for 5 min performed with 2% v sodium silicate aqueous solution was less than optimal. Even though the small bubbles are evenly distributed, the CO 2 barely reacts with the sodium silicate solution; as a result, there is still a lot of gas that escapes from the surface of the liquid.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to TEOS sodium silicate is commonly used as an ingredient for the production of mesoporous silica and silica aerogels [11,12]. The packed columns with cylindrical packing for silica precipitation have been studied previously [13]. This experiment uses spherical packing with a focus on the absorption of CO2 into * Corresponding author : sriemuljani.tk@upnjatim.ac.id sodium silicate solution by controlling the gas flow rate.…”
Section: Introductionmentioning
confidence: 99%